Plasmonic Resonances of Metal Nanoparticles: Atomistic vs. Continuum Approaches - Bonatti, Luca; Gil, Gabriel; Giovannini, Tommaso; Corni, Stefano; Cappelli, Chiara (Frontiers in Chemistry, 2020)
The fully atomistic model, $ω$FQ, based on textbook concepts (Drude theory, electrostatics, quantum tunneling) recently developed by some of the present authors in Nanoscale, 11, 6004-6015 is applied to the calculation of the optical properties of complex Na, Ag and Au nanostructures. In $ω$FQ, each atom of the nanostructures is endowed with an electric charge, which can vary according to the external electric field. The electric conductivity between nearest atoms is modeled by adopting the Drude model, which is reformulated in terms of electric charges. Quantum tunneling effects are considered by letting the dielectric response of the system arise from atom-atom conductivity. $ω$FQ is challenged to reproduce the optical response of metal nanoparticles of different size and shape and its performance is compared with continuum Boundary Element Method (BEM) calculations.